O curso de graduação em farmácia e o hospital de ensino de uma universidade pública do nordeste brasileiro: contribuições do laboratório de análises clínicas - Melo, Adriano Cavalcante (2020)
This academic work concluding the Professional Master's Degree in Health Education (MPES), from the Federal University of Alagoas (UFAL), meeting the premises of this type of post-graduation, consists of a research and an intervention product, both based on problems arising from the professional field. Thus, this research aimed to know the contributions of the Supervised Curricular Internship within the scope of Clinical Analysis, through the conceptions and expectations of the graduates and the course management. It is a qualitative research, of a descriptive nature, with the Research Scenario (AC) of an undergraduate course in Pharmacy, developed in a Teaching Hospital of a public University in the northeast of Brazil, as a research scenario. To obtain the data, a Focus Group (FG) was conducted with five graduates of both sexes and a semi-structured interview with the course management. The collected data were analyzed in the light of content analysis, from which three categories emerged: The Supervised Curricular Internship as the locus of professionalization; Perceptions about the factors that hinder the development of learning during the Internship in AC; Perceptions about the factors that facilitate the development of learning during the AC Internship. The paths pointed out by the discourses of graduates and the management of the Pharmacy course revealed that there are opportunities for establishing relationships between theory and practice in the professional routine of the Internship in AC. However, they also emphatically indicated the need to promote initiatives for reflection and evaluation of the practices developed in the internship, in line with the training objectives of the course, through joint planning of activities, as well as investments in teacher development by preceptors. Based on this appraisal of the internship, it can be concluded that there are aspects that can be realigned and provide concrete subsidies for improving the quality of the curriculum of the undergraduate course, the scenario of this study. In this sense, based on the suggestions issued by the graduates participating in this research, the construction of an intervention product, a conclusive technical research report, was developed. In this product,investment in preceptorship is defended through a program - “Knowing, Planning, Training and Evaluating: Program for the Valuation of Preceptorship of the Internship in Clinical Analysis” (PVP) - as a suggestion to the course managers. The title makes clear the purpose and sequence of intentions of the project, which covers four phases: the first, making known to the preceptors the Pedagogical Political Project (PPP) of the course that guides the training; the second, do the joint planning of the Internship in AC, based on the learning objectives that make up the PPP of the course; the third, promoting training based on the demands of the preceptors; and, finally, the fourth phase, to evaluate the internship to improve this training period. Therefore, it is considered that the results of this research, as well as the product generated, are relevant to provide a reflection on the Supervised Curricular Internship, aiming at the improvement and strengthening in the training of the pharmaceutical professional, focused on health care and the transformation of reality Social.